Pengaruh Iklan Spotify Premium terhadap Minat Beli Mahasiswa Politeknik Negeri Bandung - Giovanni Azel (International Journal Administration, Business & Organization, 2022)
This study aims to assess the impact of Spotify Premium advertisements on the purchasing interest of students at Bandung State Polytechnic, Indonesia. The method employed is quantitative descriptive, utilizing a questionnaire as the data collection tool. The respondents consist of 100 students from Bandung State Polytechnic, Indonesia who use Spotify as their music streaming platform. Data analysis involves techniques such as frequency analysis and simple regression. The research findings indicate that Spotify Premium advertisements have a 35.4% influence on the purchasing interest of students, while the remaining 64.6% is influenced by other variables not explored in this study.